Vapour pressures, enthalpies and entropies of sublimation of para substituted benzoic acids - Manuel J S Monte (2010)
The vapour pressures of six para-substituted benzoic acids were measured using the Knudsen effusion method within the pressure range (0.1-1 Pa) in the following temperature intervals: 4-hydroxybenzoic acid (365.09-387.28) K; 4-cyanobenzoic acid (355.14-373.28) K; 4-(methylamino)benzoic acid (359.12-381.29) K; 4-(dimethylamino)benzoic acid (369.29-391.01) K; 4-(acetylamino)benzoic acid (423.10-443.12) K; 4-acetoxybenzoic acid (351.28-373.27) K. From the temperature dependence of the vapour pressure, the standard molar enthalpy, entropy and Gibbs energy of sublimation, at the temperature 298.15 K, were derived for each of the studied compounds using estimated values of the heat capacity differences between the gaseous and the crystalline phases. Equations for estimating the vapour pressure of para substituted benzoic acids at the temperature of 298.15 K are proposed.